Whom does the Amur belong to? Russian-Chinese Relations in the late 19th - early 20th Centuries - Y Sakon (RUDN Journal of Russian History, 2011)
The article is devoted to some peculiarities in the Russian-Chinese relations in the late 19th - early 20th centuries. The author considers the development of navigation on the Amur and the Sungari rivers due to the economic development of Manchuria and the Amur Region. The author points out some contradictions between the Russian and Chinese authorities in the issues of navigation in the Amur region.